2017
DOI: 10.1073/pnas.1703309114
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency hippocampal–cortical activity drives brain-wide resting-state functional MRI connectivity

Abstract: The hippocampus, including the dorsal dentate gyrus (dDG), and cortex engage in bidirectional communication. We propose that low-frequency activity in hippocampal-cortical pathways contributes to brain-wide resting-state connectivity to integrate sensory information. Using optogenetic stimulation and brain-wide fMRI and resting-state fMRI (rsfMRI), we determined the large-scale effects of spatiotemporal-specific downstream propagation of hippocampal activity. Low-frequency (1 Hz), but not high-frequency (40 Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 87 publications
(110 reference statements)
6
77
2
Order By: Relevance
“…Photostimulation at frequencies ranging from 5 to 20 Hz indicated spatially overlapping results ( Supplementary Fig. 10e), in contrast to previous research 39 . In fact, the nonspecific, visually-associated response amplitude was stronger at lower frequencies ( Supplementary Fig.…”
Section: Functional Connectome Of the Entl Revealed By Optogeneticscontrasting
confidence: 99%
“…Photostimulation at frequencies ranging from 5 to 20 Hz indicated spatially overlapping results ( Supplementary Fig. 10e), in contrast to previous research 39 . In fact, the nonspecific, visually-associated response amplitude was stronger at lower frequencies ( Supplementary Fig.…”
Section: Functional Connectome Of the Entl Revealed By Optogeneticscontrasting
confidence: 99%
“…These data suggest that Olfr de-repression in PGNs coincides with the cascade of transcriptional responses to recent strong activation, which naturally occurs in CA1 PGNs during spatial tasks and is critical for long-term memory formation [33][34][35] .…”
Section: A Sub-population Of Activated Pgns Express a Single Olfr Genmentioning
confidence: 73%
“…Previous work has explored how optogenetic stimulation at different frequencies may also result in different magnitudes of regional activation and static functional connectivity [43][44][45] . Furthermore, a recent study has also demonstrated how driving neuronal activity with optogenetics results in static patterns of effective connectivity as determined through dynamical causal modeling 46 .…”
Section: Discussionmentioning
confidence: 99%